Combustion characteristics of synthetic gasoline in modern charge boosted GDI Engines - Rockstroh, Manuel Tobias (Sasol Advanced Fuels Laboratory, 2015)
Sasols synthetically derived gasoline blending components have traditionally been combined predominantly according to process economics to formulate commercial fuel blends that meet in-house fit-for-purpose requirements and the legislated fuel specifications in South Africa. In this study the potential for optimisation of a fuel blend using full boiling range synthetic blending components to enhance its performance in a modern charge boosted gasoline direct injection engine was investigated. An evaluation of detailed analytical fuel chemistry data was conducted followed by laminar ame speed experiments in a constant-volume combustion bomb apparatus in order to characterise the combustion behaviour of the blending components according to their characteristic chemical properties. A matrix of test fuels was established by splash blending the synthetic components with a commercial synthetic reference fuel. The performance of the fuels was subsequently evaluated using a modern, charge boosted, single cylinder GDI research engine. While the engine operation was verified to be in the negative-K region using model fuel components, anomalies in de fining the K-value using the synthetic blends were discovered. A fuel blending model was composed to allow prediction of linear and non-linear fuel properties of user de fined synthetic blend ratios. By integrating an engine performance test fuel scoring system, the model could be used to de fine optimal fuel blends through selection of a desired performance criterion while constraining the optimisation process to adhere to the national legislated gasoline specifications. Four final fuel blends were optimised according to best power output, gravimetric specific fuel consumption, volumetric specific fuel consumption and specific legislated emissions. A fifth blend was optimised for highest power output with no regard for fuel property specifications other than Reid vapour pressure. The performance of the optimised blends was evaluated on the test engine and the results indicated the potential to positively affect the performance characteristics of a synthetic fuel blend for use in a modern spark ignition engine. This study demonstrates a methodology for optimisation of a synthetic fuel to user-selected performance criteria and it is believed that this work represents a novel and valuable contribution to this field.